Perancangan Sistem Pemetaan Wilayah Calon Pelanggan Dengan Menggunakan Qgis Pada Pt. Indonesia Comnets Plus (Icon+) Sbu Bengkulu - Nurfitri Andayani; Ari Maulana; Wimmy Hartawan (Jurnal Informatika, 2022)
Quantum GIS is an open source Geographic Information System (GIS) software. Geographic Information Systems (GIS) can be used or run on various operating systems. QGIS aims to be a GIS for displaying GIS data and providing common functions and features. This research was conducted to design a mapping system for prospective customers using QGIS at PT. Indonesia Comnets Plus (ICON+) SBU Bengkulu. The research method uses the literature study method, the observation method and the interview method. The benefit of the system designed is that for marketing ICON+ SBU Bengkulu, there is no need to guess the location of network installation in areas where customer information is not yet clear.